Hardness and Microstructure Characteristics in Iron Sand Casting from Ampenan Beach with Used Canned Aluminum Alloy - Habibi, Angga Wildan; Sinarep, Sinarep; Alit Triadi, Anak Agung (Politeknik Siber Cerdika Internasional, 2025)
Iron sand from Ampenan Beach, Lombok, which contains 74.5% Fe₃O₄, holds significant potential as a local raw material for metal casting. However, its mechanical properties, particularly hardness and microstructural uniformity, often require improvement for industrial applications. This study aims to investigate the effect of adding used aluminum can alloy on the hardness and microstructure of iron sand casting. The experiment was designed using a Completely Randomized Design (CRD) with aluminum content variations of 0%, 2%, 4%, 6%, and 8%, each repeated three times. The aluminum used was sourced from recycled beverage cans with a purity of 98.7%. Hardness tests were conducted using Brinell, Rockwell, and Vickers methods, while microstructure was analyzed through optical microscopy. The results showed that the addition of aluminum significantly increased material hardness, with the optimal result achieved at a 6% aluminum composition, resulting in a 28.8% increase in Brinell hardness compared to the control sample. Microstructural refinement was observed, with a grain size reduction from 50.0 μm at 0% Al to 25.0 μm at 6% Al, accompanied by the formation of a ferrite matrix with evenly distributed Al₄C₃ and Fe₃Al phases and a transformation in graphite morphology from lamellar to nodular. However, an excess of aluminum (8%) reduced hardness due to over-alloying and phase clustering. These findings suggest that optimizing the composition of recycled aluminum alloys can enhance the mechanical performance of locally sourced cast materials, supporting sustainable practices in metallurgy.